TRENDS IN MOBILE JOURNALISM IN MODERN MEDIA. - Murodjonova Iroda Shokhidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article is devoted to the study of the role of mobile journalism in the media system. The development of this direction, in particular, involves the use of mobile devices in journalism. Advantages, disadvantages and opportunities of mobile journalism development are highlighted. Its place in relation to traditional journalism is determined.